1985
DOI: 10.1148/radiology.156.1.4001409
|View full text |Cite
|
Sign up to set email alerts
|

Objective assessment of mammography systems. Part I: Method.

Abstract: The authors have developed an experimental method for simultaneous determination of dose and image parameters in mammography. A global and objective quality concept, the image quality index, is proposed and its reliability demonstrated by tests of reproducibility. Objective quality tests and subjective evaluation by radiologists showed good correlation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…contrast, resolution, and noise) were measured using the items available in the IQI test object (6,7) . The films were digitised with an ACS 100 Agfa scanner having a nominal resolution of 2400 dpi (dots per inch) and a dynamic range of 12 bits.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…contrast, resolution, and noise) were measured using the items available in the IQI test object (6,7) . The films were digitised with an ACS 100 Agfa scanner having a nominal resolution of 2400 dpi (dots per inch) and a dynamic range of 12 bits.…”
Section: Methodsmentioning
confidence: 99%
“…Objective methods Pseudo-objective methods IQI (6,7) NIJ (8) CD-M (8) FER (9) NRT (10) TMAX (11) TMAM (11) MTM (12) NEWC (13 objective methods, the IQI is the most sensitive method. However, its sensitivity is relatively low in comparison with other common scoring methods involving observers.…”
Section: Film Refmentioning
confidence: 99%
“…The precision on the IQI measurements is in the order + 0.005 mm. This method is fully objective and has been described elsewhere [14,15]. The mammograms were digitized with an ACS 100 Agfa scanner having a nominal resolution of H u m and a dynamic range of 12 bits.…”
Section: Methodsmentioning
confidence: 99%
“…detection of small object of high contrast) was considered to discriminate centres belonging to the trade-off area and non-optimized centres. Nevertheless, several studies have shown a good correlation between the IQI scores and the subjective image quality assessment [14,18]. To check if the analysis was not test object related, the results of Figure 2 were plotted with the type of test object regularly used locally (see Figure 5).…”
Section: Image Quality and Dosementioning
confidence: 99%
“…Some examples are given in the following paragraphs. Hessler et al (1985) have defined an image quality index (IQI) for film-screen systems as the diameter of the smallest visible object with a high probability of correct decision. This index depends on the three quantities, which have been described in Sects.…”
Section: Other Image-quality Figuresmentioning
confidence: 99%